Uveitis-Glaucoma-hyphema Syndrome - Gur, Zvi; Tsumei, Erez; Achiron, Asaf (Nepalese Journal of Ophthalmology, 2016)
After 20 years of catarct surgery, a 66 years old man has found to have subluxtaed intraocular lens with satbilizing haptic protuding through the pupil